New deep-water species of Augaptilidae (Multicrustacea, Copepoda, Calanoida) from the Arctic Ocean - Andronov, Vladimir N.; Kosobokova, Ksenia N. (Zootaxa, 2024)
Two new species of the calanoid copepod family Augaptilidae are described from specimens collected from bathypelagic depths of the Arctic Ocean. The female of Euaugaptilus verae sp. nov. can be distinguished from other congeneric species by 1) the Md tooth arrangement, 2) the structure of Mx1, and 3) the lack of external spines on Re2 and 3 of the female P5. The female of Alrhabdus antjeboetiusae sp. nov. can be distinguished from the only species of this genus, A. johrdeae Grice, 1973, by 1) the shape of the rostrum, 2) absence of paired spinal protrusions at the posterior corners of the last pedigerous somite, 3) position of spermatheca on the genital double-somite, 4) the Md tooth arrangement, and 5) P5 endopod 1-2 lacking modified medial setae. Both species were collected in the deepest regions of the Eurasian and Canadian Basins of the Arctic Ocean in the water layers between 1000 m and the seafloor.